Kesesuaian lahan untuk pengembangan tanaman kayu putih dan implikasinya terhadap teknik silvikultur - Ronggo Sadono; Djoko Soeprijadi; Pandu Yudha Adi Putra Wirabuana (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Cajuput is a plant that plays an important role for forest industry development. Its leaves contain essential oil and become one of the non-timber forest products. The productivity of cajuput leaves is affected by certain factors, one of them are the level of land suitability. This study investigated the land suitability for cajuput establishment and its inference on silviculture strategy. Study location was situated in Forest Resort Gubugrubuh, Gunungkidul District. Data collection was conducted in 3 site that converted as the priority site of cajuput plantation namely site 75, site 78, and site 80. We used 6 indicator of land attributes including altitude, slope, rainfall, temperature, soil acidity, and soil organic carbon. The assessment of land suitability was determined by qualitative approach using storie and root square method. The result showed the level of land suitability was classified into N1 (currently not suitable) referring to the storie method, meanwhile it was categorized into S3 (marginally suitable) according to the root square method. This study also discovered the distinctive land attributes which became the limiting factors of cajuput growth in each site. The best silviculture strategies for supporting cajuput development in each site were terrace construction, plant distance management, and fertilization.